Balanced substrate integrated waveguide bandpass filter with high selectivity and common‐mode suppression. Issue 2 (1st January 2015) - Chu, Hui; Li, Peng; Chen, Jian‐Xin
Abstract : A new method of designing balanced (differential) bandpass filters (BPFs) with high selectivity and common‐mode suppression is proposed and implemented by taking advantage of the existence of multiple substrate integrated waveguide cavity modes. The major design concept is by properly choosing, feeding and coupling dual‐mode cavities operating at TE102 and TE201 modes so as to not only provide capabilities to realise the desired differential‐mode passband associated with two transmission zeros, but also generate high common‐mode suppression over a wide range. Two X‐band BPFs with different internal coupling mechanisms are then proposed and designed. The two design examples having the same centre frequency of 10 Hz and respective passband width of 300 and 270 Hz are fabricated for demonstration. High selectivity is observed for both filters. Meanwhile, c is ∼37 dB for the first design example, whereas it is improved to 48.5 dB for the second one with multi‐layered structure. Good agreement can be observed between simulated and measured performances in the authors' study.